Kant’s Clandestine Meeting with Diderot in favor of Ethical Atheism - R. Aramayo, Roberto (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Here the intellectual conversation that Kant had with Diderot in the field of ideas is recounted, proving a great coincidence between the approaches of both in relation to ethical atheism, that is, with that emancipation that ethics must have with respect to any instance or external code, although one did it symphonically with his critical system and the other as rhapsodic as it was fragmentary. On the other hand, it is emphasized that both expressed their commitment and political interventionism at the end of their respective careers.